Project Initiatives on Inclusive and Equitable Use of Artificial Intelligence in Education: Lessons Derivable for Policy Direction in Nigeria - Ojokheta, Kester; Omokhabi, Abiola Adiat (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
This paper reviewed some project initiatives on inclusive and equitable use of artificial intelligence (Al) in education with a view of guiding education policy-makers and stakeholders in the development of similar project initiatives in Nigeria. The gap in extant literature on policy direction for the development of inclusive and equitable use of Al in education in Nigeria necessitated the paper. It began with a discussion of the general overview of Al and the unprecedented revolution it has created in the education delivery. It further discussed the advantages of the Al application in education as well as the challenges and controversies associated with it particularly the generative Al (GenAl) systems which are rapidly spreading in the education sector. It also discussed UNESCO’s recommendations of the appropriate use of GenAl in education to genuinely benefit and empower teachers, learners and researchers. It advocated the necessity of Nigerian government to develop a policy framework for the responsible use of GenAl in education and research. Most importantly, the paper identified some large-scale project initiatives on inclusive and equitable use of Al in education and discussed the lessons derivable from the project initiatives for policy direction in the development of similar projects in Nigeria. The paper recommended, among others, special funding on the development of inclusive and equitable Al apps in the education budgetary allocation and private sector partnership/collaboration in funding in the development of such Al apps.